PERANCANGAN SITUS PENJUALAN ONLINE PADA TOKO 88 JUNGKAT - Fernando, Darmadi Andrew; Iskandar, Riyadi Jimmy; Willay, Thommy (LPPM Universitas Widya Dharma Pontianak, 2024)
The conventional sales system at Toko 88 Jungkat has resulted in various issues like slow service, the unavailability of a reporting system, and inaccuracies in sales and inventory data recording. The research method used is the descriptive research method. Data collection techniques include interviews, observations, and literature studies. The applied system analysis and design technique is object-oriented, utilizing Unified Modeling Language (UML) diagrams as the modeling tool. The system design applications use HTML, CSS, PHP, JavaScript, Visual Studio Code, XAMPP, StarUML, MariaDB, and Bootstrap. The proposed online sales system allows customers to access product information instantly, place orders and make payments without queuing, track shipped orders, download order invoices, and request returns. In addition, the admin can manage all transactions, while the admin and the owner can do sales reports, inventory records, and print returns. Computerized sales systems offer more accurate, systematic, and error-minimized results due to the automation provided by the system. It is necessary to have training for website admin positions and further analysis of a larger target market by a selling goods system in large quantities. Keywords: Designing, system, information, sales, web